Inhibitory Control Training A Multidisciplinary Approach - Palermo, Sara; Bartoli, Massimo (IntechOpen, 2020)
Inhibitory control is a critical neurocognitive skill for navigating cognitive, social, and emotional challenges. It rapidly increases during the preschool period and is important for early cognitive development, as it is a crucial component of executive functioning, self-regulation, and impulsivity. Inhibitory control training (ICT) is a novel intervention in which participants learn to associate appetitive cues with inhibition of behavior. It is being considered a promising approach in the treatment of psychopathology and appetitive behaviors. This book aims to bring together knowledge on the topic, considering research, clinic, and forensic field of intervention. Indeed, this book can be considered an excellent synopsis of perspectives, methods, empirical evidence, and international references.